Depression, anxiety and stress among undergraduate science students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (2015)
Objectives: This study aimed to determine the prevalence of depression, anxiety and stress symptoms among undergraduate Science students and to detect the sources of stressors and their relationship with these symptoms. Material and methods: A total of 194 undergraduate students from Kulliyyah (Faculty) of Science, International Islamic University Malaysia participated in a questionnaire-based study using the Depression Anxiety, Stress Scale (DASS-21) to assess rate of depression, anxiety and stress symptoms. Then the sources of stressors were identified by asking the students to tick “yes” for the item that they considered as the most stressful factor which they experienced during the current academic year from a list of possible sources of stressors which were chosen depending on previous studies Results: It was found that 13.9%, 51.5 % and 12.9% of the students have clinically significant depression, anxiety and stress symptoms respectively. Young students aged 21 years and below had a statistically significant association with depression, anxiety and stress. While first year students had significant association with depression. Regarding the source of stressors, the top ten stressors decided by the students were mainly academic and personal factors. Conclusion: Emotional disturbances in the form of depression, anxiety and stress are existing in high rate among undergraduate science students that require early intervention. Factors including feeling of incompetence, lack of motivation to learn and difficulty of class work can be considered as source of stressors that may precipitate for depression anxiety and stress.